Pengaruh Model Project Based Learning Berbantuan Alat Peraga Kotak Sifat Cahaya terhadap Hasil Belajar Ilmu Pengetahuan Alam (IPA) Kelas V SDN 29 Woja - Uswatun Hasanah; Muhammad Erfan; Mansur Hakim (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aimed to determine the effect of the Project Based Learning (PjBL) model assisted by a light properties box teaching aid on the science and social studies (IPAS) learning outcomes of fifth-grade students at SDN 29 Woja. This research employed a quantitative approach with a quasi-experimental research design using the Nonequivalent Control Group Design. The research sample consisted of class V A as the experimental class and class V B as the control class. Data collection techniques included learning outcome tests and observation sheets. The validity test results showed that all test items were valid with r-count values greater than the r-table value of 0.2353, and the reliability test obtained a Cronbach’s Alpha value of 0.927, indicating that the instrument was reliable. The normality test results indicated that the pretest data of the control class were normally distributed, while the other data were not normally distributed. The homogeneity test results showed significance values of 0.380 and 0.864, indicating that the data were homogeneous. The hypothesis test using the Independent Samples T-Test obtained a Sig. (2-tailed) value of < 0.001 < 0.05, meaning that H₀ was rejected and Hₐ was accepted. The findings revealed that the Project Based Learning (PjBL) model assisted by a light properties box teaching aid had a significant effect on students’ IPAS learning outcomes at SDN 29 Woja. The observation results of learning implementation in the experimental class obtained a percentage of 91.96%, categorized as very good. Therefore, the Project Based Learning model assisted by a light properties box teaching aid can improve students’ IPAS learning outcomes.